2021
DOI: 10.3390/jcs5020061
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Multifunctionality in 3D-Printed Polystyrene-Boron Nitride Nanotubes (BNNT) Composites

Abstract: In this work, polystyrene (PS) and boron nitrides nanotubes (BNNT) composites were fabricated, prepared, and characterized using modified direct mixing and sonication processes. The polymer composites were extruded into filaments (BNNTs at 10 wt. %) for 3D printing, utilizing the fused deposition modeling (FDM) technique to fabricate parts for mechanical and thermal applications. Using a direct mixing process, we found that the thermal conductivity and the mechanical strength of the PS-BNNT composite were resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…They found that a better stability to oxidation and an increment by 21% in the elastic modulus can be obtained by the incorporation of 1 wt% of BNNTs. Akintola et al [ 17 ] studied the mechanical and thermal performances of the BNNT/PS composites. The results showed that the storage modulus, ultimate tensile strength, and thermal stability of the composites were significantly improved by the introduction of BNNTs.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a better stability to oxidation and an increment by 21% in the elastic modulus can be obtained by the incorporation of 1 wt% of BNNTs. Akintola et al [ 17 ] studied the mechanical and thermal performances of the BNNT/PS composites. The results showed that the storage modulus, ultimate tensile strength, and thermal stability of the composites were significantly improved by the introduction of BNNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The weight of BNNTs over 80 min was unattainable as the sample melted and stuck to the container. A slight weight gain during the initial 40 min was detected for pure BNNTs, due to the oxidation of BN 31 and boron 32 . The formation of B 2 O 3 results in a rapid weight gain and the relevant chemical reaction following Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] In recent work, dispersions of BNNTs in solvents, including dimethyl formamide (DMF) and ethanol, have been integrated with polymer matrices to produce composites and bers. 12,[20][21][22] Particularly, signicant improvement in thermal conductivity was obtained for BNNT-based composites prepared by vacuum ltration of aqueous dispersions of nanotube/polymer mixtures. [22][23][24] However, ber spinning and mechanical property enhancement of BNNT assemblies remain to be challenging.…”
Section: Introductionmentioning
confidence: 96%